Analysis of Computer Crime Incidents (Texas Journal of Multidisciplinary Studies, 2022)
"Algorithms for predicting measures to ensure information security based on the analysis of computer crime incidents", computer crime, its types and reasons for committing were analyzed. In Maskur's article, a network traffic analysis algorithm generated several time series between different sets of infrastructure as a result of short-term forecasting and monitoring. If each observed value does not exist within the confidence interval, such information is called a risk, that is, an incident